Photoelectrocatalytic oxidation of remazol turquoise blue and toxicological assessment of its oxidation products - Osugi, Marli E.; Umbuzeiro, Gisela A.; De Castro, Francisco J. V.; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2006)
The ability of photoelectrocatalytic oxidation to degrade the commercially important copper-plitalocyanine dye, remazol turquoise blue 15 (RTB) was investigated. The best experimental condition was optimized, evaluating the performance of Ti/TiO2 thin-film electrodes prepared by sol-gel method in the decolourization of 32 mg L-1 RTB dye in 0.5 mol L-1 Na2SO4 pH 8 and applied potential of +1.5 V versus SCE under UV irradiation. Spectrophotometric measurements, high performance liquid chromatography, dissolved organic carbon (TOC) evaluation and stripping analysis of yielding solution obtained after 3 h of photoelectrolysis leads to 100% of absorbance removal from wavelength of 250-800 nm, 79.6% of TOC reduction and the releasing of up to 54.6% dye-bound copper (0.85 mg L-1) into the solution. Both, original and oxidized dye solution did not presented mutagenic activity with the strains TA98 and WOO of Salmonella in the presence and absence of S9 mix at the tested doses. Nevertheless, the yielding photoelectrocatalytic oxidized solution showed an increase in the acute toxicity for Vibrio fischeri bacteria, explained by copper liberation during treatment. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: remazol turquoise blue; mutagenic activity; photoelectrocatalytic oxidation